Moradores de rua na cidade do Guarujá/SP : condições de vida, saúde, emoções e riscos - Aguiar, Maria José Gomes de (2014)
This study aimed to know the people on the streets, living conditions, health - disease and their access to public institutions providing health care. We chose the city of Guaruja, in Santos, for being one of the places of highest demand of this population. Its specific objectives: a) outline the profile of the homeless city of Guaruja - SP, according to age, education, work status, family structure and reason lies in the streets; b) Check for diagnosis of chronic and / or comorbidity and perceived health - disease of the homeless city of Guarujá - SP; c) Identify the means of access to and control of chronic disease comorbidities in places providing health services in the city of Guarujá - SP; d) assess the perception of risk and the impact of social stigma on the emotions of the homeless city of Guaruja - SP. Qualitative research was used in this work, because this approach works with a plethora of meanings, motives, aspirations, beliefs, values and attitudes acquired in the historical and social process that set of human phenomena are understood as part of social reality. The results confirmed male dominated, with low education leading them to provide informal jobs and low quality; most respondents have compromised to the point of interfering with their health conditions of survival feelings and emotions like fear sadness, longing and abandonment of the family were evident during this research. It was also noted in the reports attitudes of violence against this population by civil guards the city, which increases the risk experienced by those who only have the streets for shelter. The access to these health services is made primarily by the Emergency Unit and the Emergency PSUs when they are accompanied or referred to this service. The analysis and discussion of the results was performed from three angles: Axis 1: Living Conditions; Axis 2: Health, disease and access to health services; Axis 3 and discussed the representations of the homeless on health and disease. We conclude that the city of Guarujá, as well as many other Brazilian cities, still has a long way to go in serving the population. Has need to implement municipal social policies in accordance with the National Policy for the homeless population that recognizes their rights and guarantee the minimum conditions of citizenship.